Eurovision 2023 Cultural Relations Snapshot: A snapshot from the forthcoming cultural relations, soft power and shared values research - Baker, Catherine; Atkinson, David; Burgess, Glenn; Grabher, Barbara; Howcroft, Michael (British Council, 2025)
About this research In May 2023, Liverpool and the BBC hosted the Eurovision Song Contest on Ukraine’s behalf. This was the first time since 1980 that Eurovision has not been hosted in the previous winning country, and the first time a winner has ever been unable to host because the country is under attack. Researchers at the University of Hull with consultants from the University of Brighton, University of Glasgow, and Royal Holloway, University of London are investigating the cultural relations and ‘soft power’ impact of Eurovision for a study commissioned by the British Council in partnership with Liverpool City Council and DCMS. The study has three pillars: • A literature review surveying the state of the art in research on Eurovision and other largescale cultural and competitive events. • A tracker survey exploring the impact of Eurovision on members of the public in 5 European countries. • Interviews exploring how stakeholders co-operated to create the narrative of Liverpool, the BBC and the UK hosting Eurovision on behalf of Ukraine. We’ve prepared this snapshot ahead of the publication of the full research in January 2023 for the upcoming event ‘Liverpool Calling – And the results are in!’.